Evaluation of Mineral Contents of Greenhouse Plant Wastes in Antalya Region - Sonmez, Sahriye; Citak, Sedat; Sonmez, Ilker; Kaplan, Mustafa (Asian Journal of Chemistry, 2010)
This study was carried out to determine the amounts of plant wastes coming out from tomato, pepper, cucumber and eggplant greenhouses which are widely grown in Antalya region at the end of the growing season and the mineral contents of plant wastes. For this purpose, plant samples were taken from the greenhouses in which tomato, pepper, cucumber and eggplant was grown in Antalya Region and separated from stem, leaf, fruit and root to analyze N, P, K, Ca, Mg, Fe, Mn, Zn and Cu contents. The fresh and dry weights of plant samples were determined. According to results, the fresh weights of tomato, pepper, cucumber and eggplant wastes at the end of growing season were determined as 584745, 48014, 89757 and 54605 tons ha-1, respectively and it was determined to be total of 777112 tons ha-1 of plant wastes and to be wasted 7043 tons ha-1 nutrients with tomato plant wastes, 832 tons ha-1 nutrients with pepper plant wastes, 1435 tons ha-1 nutrients with cucumber plant wastes and 904 ton ha-1 nutrients with eggplant wastes. In addition, with these plant wastes, nutrients such as N, P2O5 and K2O, which are equal to 7159 tons ha-1 in Antalya, were lost instead of being used as fertilizer. It was determined that use of these wastes by composting enables recycling of substantial amounts of nutrients and use of these composts especially on the soils which has low organic matter content may create important advantages. However, it was concluded that significant advantages in terms of both environment and economy could be acquired by the establishment of waste collecting and composting facilities enabling the recycling of the materials named as wastes.